Visual field fluctuations correlating with the menstrual cycle in a patient with optic pathway glioma. Issue 4 (7th April 2020) - Jacobson, Adam; Leonard, Marcia; Robertson, Patricia; Bohnsack, Brenda L
Abstract : Optic pathway gliomas are commonly associated with vision loss in children. We describe an 18-year-old woman with neurofibromatosis, type 1 and an optic nerve glioma who showed reproducible visual field defects that worsened midmenstrual cycle and returned to baseline during menses. To our knowledge, this is the first reported case of visual field fluctuations in a patient with an optic nerve glioma that correlated with her menstrual cycle.